Methane detection scheme based upon the changing optical constants of a zinc oxide/platinum matrix created by a redox reaction and their effect upon surface plasmons - Allsop, Thomas P.; Kundrat, Vojtech; Kalli, Kyriacos; Lee, Graham B.; Neal, Ron; Bond, Peter R.; Shi, Baogul; Sullivan, John; Culverhouse, Phil; Webb, David J. (My University, 2018)
We detect changes in the optical properties of a metal oxide semiconductor (MOS), ZnO, in a multi-thin-film matrix with platinum in the presence of the hydrocarbon gas methane. A limit of detection of 2% by volume with concentrations from 0 to 10% and maximum resolution of 0.15% with concentrations ranging from 30% to 80% at room temperature are demonstrated along with a selective chemical response to methane over carbon dioxide and the other alkane gases. The device yields the equivalent maximum bulk refractive index spectral sensitivity of 1.8 × 105 nm/RIU. This is the first time that the optical properties of MOS have been monitored to detect the presence of a specific gas. This single observation is a significant result, as MOS have a potentially large number of target gases, thus offering a new paradigm for gas sensing using MOSs.
Keywords: Fibre optics; Gas sensing; Localized surface plasmons; Metal oxide semiconductors; Optical sensing